Identification of novel therapeutic targets for cognitive performance and associations with brain health - Lu-Yang Zhang; Yu-Xin Liu; Yun-Hui Chu; Yun-Fan You; Luo-Qi Zhou; Sheng Yang; Ming-Hao Dong; Hang Zhang; Xiao-Wei Pang; Lian Chen; Li-Fang Zhu; Jun Xiao; et al. (Translational Psychiatry)
Abstract Cognitive dysfunction poses a significant challenge in clinical practice, but currently available drugs mainly address symptoms and have limited effectiveness in treating cognitive dysfunction associated with various neurological disorders. Mendelian randomization (MR) and colocalization analyses were conducted to explore the causal associations between 4302 druggable genes with blood and brain cis-expression quantitative trait loci (eQTLs) and cognitive performance. The causal effects of candidate druggable genes on brain structure and neurological diseases were assessed to gain insights into the underlying mechanisms. Among over 4000 druggable genes, our study identified causal associations between 72 druggable genes (41 blood eQTLs and 31 brain eQTLs) and cognitive performance. Thirteen eQTLs (six in blood: ERBB3, SPEG, ATP2A1, GDF11, CYP2D6, GANAB; seven in brain: ERBB3, DPYD, TAB1, WNT4, CLCN2, PPM1B, CAMKV) were identified as candidate druggable genes for cognitive performance. Notably, both blood and brain eQTLs of ERBB3 were negatively associated with cognitive performance (blood: OR = 0.933, 95% CI 0.911–0.956, p-value = 9.69E-09; brain: OR = 0.782, 95% CI 0.718–0.852, p-value = 2.13E-08). Moreover, these candidate druggable genes exhibited causal effects on both brain structure and neurological diseases. Our integrative analysis provides genetic evidence supporting candidate therapeutic targets for improving cognitive performance and treating neurological diseases. Furthermore, it sheds light on the possible mechanisms by which these targets affect brain structures. This finding suggested that these identified druggable genes, particularly ERBB3 and CYP2D6, hold promise as potential drug targets for enhancing cognitive performance.